2013
DOI: 10.1007/s12098-013-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Sprinkles Plus through the Integrated Child Development Services (ICDS) to Reduce Anemia in Pre-school Children in India

Abstract: Integration of a flexibly administered MNP supplementation into the ICDS is effective in reducing and treating anemia in children 6 mo to 6 y age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…Despite the fact that MNP programs reach millions of children each year [9], there are only a handful of studies that have assessed how to best implement programs using MNPs at scale [10,11,12,13,14,15,16]. Studies have documented the use of MNP in a variety of contexts including emergency settings [10], as part of rural food distribution programs [15], as part of integrated child health programs [11], and the sale of MNP through social marketing [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that MNP programs reach millions of children each year [9], there are only a handful of studies that have assessed how to best implement programs using MNPs at scale [10,11,12,13,14,15,16]. Studies have documented the use of MNP in a variety of contexts including emergency settings [10], as part of rural food distribution programs [15], as part of integrated child health programs [11], and the sale of MNP through social marketing [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented the use of MNP in a variety of contexts including emergency settings [10], as part of rural food distribution programs [15], as part of integrated child health programs [11], and the sale of MNP through social marketing [17]. Increasingly, MNPs are being integrated into large-scale infant and young child feeding (IYCF) programs [18,19]; however there is limited evidence demonstrating the impact of integrated interventions on IYCF practices and ultimately on children’s nutritional status [19].…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios realizados en el ámbito mundial, con el propósito de evaluar los efectos de los MP a diferencia de este estudio, han tomado poblaciones anémicas, encontrando que es igual de efectivo y en algunos casos con menos efectos adversos en comparación con los tratamientos convencionales [19][20][21]. Sin embargo, este estudio no fue realizado en población con anemia, ni con desnutrición aguda severa, debido a que en Colombia no está autorizado por los entes reguladores como el Instituto Nacional de Vigilancia de Medicamentos y Alimentos (invima) el uso de los MP empleados en este estudio como un medicamento para el tratamiento de ese tipo de deficiencias, sino como un alimento, lo que impide la comparabilidad con algunos estudios disponibles en las bases de datos, convirtiendo a esta investigación en una primera aproximación a la evaluación de la efectividad del producto en población colombiana sana.…”
Section: Discussionunclassified
“…Estos resultados son semejantes a los encontrados en los estudios de Hirve y Christofides [12,21] quienes observaron efectos adversos como diarrea y vómito en el grupo que recibió gotas de sulfato ferroso al comparar con los MP y placebo.…”
Section: Discussionunclassified
“…To the Editor: We read with great interest article entitled "Delivering sprinkles plus through the Integrated Child Development Services (ICDS) to reduce anemia in preschool children in India" [1]. The authors have concluded that following micronutrient powder supplementation; a reduction in anemia by 50-30 % was achieved in children.…”
mentioning
confidence: 99%